Hydrological assessment using stable isotope fingerprinting technique in the Upper Chao Phraya river basin - A. Putthividhya; J. Laonamsai (Lowland Technology International, 2017)
This study is focusing to assess the spatial and temporal distribution of rainfall using water stable isotope technique as well as the surface water-groundwater interactions for the aquifer systems in the Upper Chao Phraya river basin systems. Local precipitation, surface water, and groundwater along the main river courses and their tributaries are directly samples. Massive precipitation isotopic composition database from existing IAEA monitoring network (GNIB) along with local Bangkok precipitation isotopic signature are compared with precipitation from Chiang Mai province to better identify the rainfall isotopic compositions. In addition to the isotopic differentiation of precipitation in the area, its impacts on isotopic characteristics of surface water and groundwater are additionally explored. LMWLs (Local Meteoric Water Line) for local rainfall in Bangkok and Chiang Mai are generated with some seasonal variation due to rain out effect. Surface water is influenced by evaporation at some degree, revealing that rainfall may not be the primary source of surface water. Yom river’s isotope values are far more D and 18O-enriched compared to Ping’s and Nan’s, suggesting the mixing of groundwater with river water and/or the source of surface water may come from dry-period precipitation. Stable oxygen and hydrogen isotopes in groundwater fall on an evaporation line, and are thus indicative of the effects of high evaporation rates through the top surficial material. The isotopic similarity with the more depleted GD and G18O of groundwater samples suggests the potential mixing of groundwater with river water by different mixing processes (54% from river water and 46% from rainfall). The results show correlations in the isotope signature of shallow (< 50 m deep) and deeper aquifer (> 50 m deep) which may be associated with hydraulic connection and/or similar hydrogeological conditions. d-excess stable isotope analyses are beneficial to identify the relative contributions of the wet and dry seasonal sources to the groundwater recharge. The results indicate that groundwater sources are composed of a 71.4% wet seasonal sources and a28.6% dry seasonal sources.